(untitled) - Robert J. Brooker (Menlo Park, California, 1999)
Genetics: Analysis and Principles, Professor Robert J. Brooker reinforces that connection by emphasizing the relevance and significance of the scientific method used by geneticists. Thirty-six text-integrated experiments reveal the "how" and "why" behind the most important research that led to our current knowledge of the science. The overarching theme of the book, the important link between genes and traits, is mirrored in the cover image.
Keywords: Genetics,Di truyền